RETRACTED: Synthesis, Characterization, and Biological-Pharmacological Evaluation of New Phosphazenes Bearing Dioxybiphenyl and Schiff Base Groups (Retracted Article) - Cil, Erol; Tanyildizi, Mehmet Ali; Ozen, Furkan; Boybay, Mustafa; Arslan, Mustafa; Gorgulu, Ahmet Orhan (WILEY-V C H VERLAG GMBH, 2012)
A new spirocyclophosphazene, 2,2-bis(2-formylphenoxy)-4,4,6,6-bis[spiro(2',2?-dioxy-1'-1?-biphenylyl)]cyclotriphosphazene (3), was obtained from the reaction of 2,2-dichloro-4,4,6,6-bis[spiro(2',2?-dioxy-1'-1?-biphenylyl)]cyclotriphosphazene (2) with 2-hydroxybenzaldehyde. New phosphazene derivatives bearing Schiff base and dioxybiphenyl groups have been synthesized by the reactions of 3 with different amines. The structures of the compounds were defined by elemental analysis, IR, 1H, 13C, and 31P NMR spectroscopy. All the synthesized compounds were screened for their antibacterial activity against both types of Gram-negative and Gram-positive bacteria. The most potent antibacterial compound of this series was compound 12 which has the low MIC value of 3.750.9375 mu g/mL. Both minimal inhibitory concentrations (MIC) and inhibition zones were determined in order to monitor the efficacy of the synthesized compounds. New compounds were also screened for anticonvulsant, CNS depressant, and sedative-hypnotic activity. After i.p. injection to mice at doses of 30, 100, and 300?mg/kg body weight phosphazenes were examined in the maximal electroshock-induced seizure (MES) and subcutaneous pentylenetetrazole (scPTZ) induced seizure models in mice. The neurotoxicity was assessed using the rotorod method. Compounds 4, 5, and 11 were found to be active in both MES screen and scPTZ screen at 0.5?h. All except 12 showed more than 44% decrease in locomotor activity after 1?h of compound administration via actophotometer screen. CNS-depressant activity screened with the help of the forced swim method resulted in some potent compounds. Except for 7 and 12 other tested compounds were found to exhibit potent CNS depressants activity as indicated by increased immobility time.
Keywords: Antibacterial activity; Anticonvulsant; Hexachlorocyclotriphosphazene; Phosphazene; DICHLOROPHOSPHORYL-P-TRICHLOROPHOSPHAZENE; CYCLOTRIPHOSPHAZENE DERIVATIVES; LINEAR PHOSPHAZENES; OXIME-PHOSPHAZENES; THERMAL-PROPERTIES; HIGH POLYMERS; YEAST-CELLS; POLY(ORGANOPHOSPHAZENES); POLYPHOSPHAZENES; BACTERIAL; Pharmacology & Pharmacy; Chemistry